Clinical profile of refractive errors in children in a tertiary care hospital of Northern India - Mittal, Sneha; Maitreya, Amit; Dhasmana, Renu (International Journal Of Community Medicine And Public Health, 2017)
Background: Refractive errors constitute a major portion of children with visual impairment. Aim of this study was to study the pattern of refractive errors and its association with selected variables (age, sex, educational status, socioeconomic status, amblyopia and strabismus). Methods: This was hospital based observation descriptive study. The study was conducted on 781 eyes of 396 children, 5-15 years of age attending the ophthalmology OPD of a tertiary care teaching hospital of North India. Interpretation and analysis of obtained results was carried out using SPSS version 22 and non-parametric tests like Pearson Chi-square test was used. Results: Mean age of presentation was 10.90±3.16 years with male: female ratio of 1.8:1. 57.07% mothers and 70.20% fathers were intermediate and above. Number of children from lower middle socioeconomic status (40.90%) and with a positive family history of refractive errors (59.59%) was higher. 7.07% children had amblyopia and 6.06% children had strabismus. Most of the children with refractive errors were having mild (≤1.5D) refractive error (61.20%) and not using spectacles previously (78.30%). Astigmatism was found in 46.99% followed by myopia (41.23%) and hypermetropia (11.78%). The UCVA was >6/12 in 48.27% eyes. Conclusions: This study reinforces the previously reported pattern of refractive errors and its association with others variables except that a large number of children were found to have refractive errors but not using spectacles in this area. Risk of refractive error in children was associated with higher level of education of mother which has not been reported earlier.